Determinants for drug survival of methotrexate in patients with psoriasis, split according to different reasons for discontinuation: results of the prospective MTX‐CAPTURE. (11th May 2017) - Otero, M.E.; van den Reek, J.M.; Seyger, M.M.; van de Kerkhof, P.C.; Kievit, W.; de Jong, E.M.
Summary: Background: As methotrexate (MTX) is a widely used treatment for psoriasis, it is important to gain insight into the reasons for the discontinuation of MTX and to understand the determinants for drug survival. Objectives: To describe 5‐year drug survival for MTX in patients with psoriasis, split according to different reasons for discontinuation, and to identify the determinants for drug survival. Methods: Data were extracted from a prospective psoriasis registry of patients treated with MTX (MTX‐CAPTURE). Drug survival was analysed using Kaplan–Meier estimates and the determinants for discontinuation were analysed using Cox regression analysis. Analyses were split according to the reason for discontinuation: side‐effects or ineffectiveness. Results: We included 85 patients treated with MTX, with a maximum treatment duration of 5·2 years. The overall drug survival rates were 63%, 30% and 15% after 1, 3 and 5 years, respectively. The median survival was 1·8 years. Overall, 55 patients (65%) discontinued MTX for the following reasons: side‐effects (35%), ineffectiveness (26%), combination of side‐effects and ineffectiveness (13%), other reasons (16%) and 11% were lost to follow‐up. The most reported side‐effects were gastrointestinal symptoms, despite the use of folic acid in 99% of patients. Based on univariate analysis, a high Psoriasis Area and Severity Index score and a high score on the visual analogue scale for disease severity at baseline were possible determinants for a short drug survival. Conclusions: Drug survival of MTX was low with 15% of patients 'on drug' after 5 years. Side‐effects alone or in combination with inadequate disease control were more important in the context of treatment discontinuation than inadequate disease control alone. Abstract : What's already known about this topic? Methotrexate (MTX) is a widely used treatment for moderate‐to‐severe plaque psoriasis. Drug survival of methotrexate for psoriasis has not been studied in detail. What does this study add? This is the first study to describe the long‐term drug survival of MTX in patients with plaque psoriasis in daily practice, split according to side‐effects and ineffectiveness. This is the first study to identify the determinants for drug survival, split according to reasons for discontinuation. A high baseline score on the visual analogue scale for disease severity assessed by the patient may play an important role in short drug survival. Respond to this article Linked Comment:  Kirby. Br J Dermatol 2017;177 :345–346